Candida albicans biofilms and MMA surface treatment influence the adhesion of soft denture liners to PMMA resin - Martinna de Mendonça e Bertolini; Yuri Wanderley Cavalcanti; Dimorvan Bordin; Wander José da Silva; Altair Antoninha Del Bel Cury (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The effect of Candida albicans biofilms and methyl methacrylate (MMA) pretreatment on the bond strength between soft denture liners and polymethyl methacrylate (PMMA) resin was analyzed. Specimens were prepared and randomly divided with respect to PMMA pretreatment, soft liner type (silicone-based or PMMA-based), and presence or absence of a C. albicans biofilm. Samples were composed of a soft denture liner bonded between two PMMA bars. Specimens (n = 10) were incubated to produce a C. albicans biofilm or stored in sterile PBS for 12 days. The tensile bond strength test was performed and failure type was determined using a stereomicroscope. Surface roughness (SR) and scanning electron microscopy (SEM) analysis were performed on denture liners (n = 8). Highest bond strength was observed in samples containing a silicone-based soft liner and stored in PBS, regardless of pretreatment (p < 0.01). Silicone-based specimens mostly underwent adhesive failures, while samples containing PMMA-based liners predominantly underwent cohesive failures. The silicone-based specimens SR decreased after 12 days of biofilm accumulation or PBS storage, while the SR of PMMA-based soft liners increased (p < 0.01). The PMMA-based soft liners surfaces presented sharp valleys and depressions, while silicone-based specimens surfaces exhibited more gentle features. In vitro exposure to C. albicans biofilms reduced the adhesion of denture liners to PMMA resin, and MMA pretreatment is recommended during relining procedures.